Analysis Management Organizing the Hajj Pilgrimage at the Ministry of Religion of Padang City Based on Law No. 8 of 2019 - Putri Hartama, Mela; Astarie Dewi, Yenty (Munazzama: Journal of Islamic Management and Pilgrimage, 2025)
This study analyzes the management of organizing the Hajj pilgrimage at the Ministry of Religious Affairs of Padang City based on Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah. The research focuses on examining the implementation of management functions, namely planning, organizing, actuating, and controlling (POAC), in ensuring effective, efficient, and Sharia-compliant Hajj services. A qualitative research method was employed, utilizing interviews, observations, and documentation techniques, involving Hajj organizers, service officers, and related stakeholders at the Integrated Hajj and Umrah Service Center of the Ministry of Religious Affairs in Padang City. The findings indicate that the implementation of Hajj pilgrimage management has been conducted systematically in accordance with established Standard Operating Procedures (SOPs) and statutory regulations. Collaboration among relevant institutions, structured administrative services, comprehensive guidance, and continuous supervision contribute to improved service quality, safety, and comfort of pilgrims. However, challenges related to integrity and consistency in law enforcement persist, underscoring the need for ongoing evaluation and enhancement of professional and accountable management practices. This study contributes to strengthening governance and policy implementation in Hajj pilgrimage management at the local government level.